2019
DOI: 10.1002/da.22974
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase ( CYP19A1 ) gene variants, sex steroid levels, and late‐life depression

Abstract: Background: Sex differences in psychiatric disorders are common and could involve sex steroids. Aromatase, the product of the CYP19A1 gene, is the key enzyme in the conversion of androgen to estrogen. Whether CYP19A1 variants could be associated with depression differently in men and women has not been examined.Methods: This population-based study included 405 men and 602 women aged ≥65 years. A clinical level of depression (DEP) was defined as having a score ≥16 on the Center for Epidemiology Studies Depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…In Figure 3 , the core genes with a degree value ≥ 20 included CYP19A1, AR, SHBG, UGT2B7, ESR1, and ESR2, which are all relevant to the regulation of estrogens [ 43 , 44 , 45 , 46 , 47 , 48 ]. It is well documented that estrogen might exert profound effects on anxiety and anxiety-like behaviors in humans and rodents [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Figure 3 , the core genes with a degree value ≥ 20 included CYP19A1, AR, SHBG, UGT2B7, ESR1, and ESR2, which are all relevant to the regulation of estrogens [ 43 , 44 , 45 , 46 , 47 , 48 ]. It is well documented that estrogen might exert profound effects on anxiety and anxiety-like behaviors in humans and rodents [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, specific alterations in cortisol and sex steroid levels as well as psychiatric disorders were reported in women with 21-hydroxylase deficiency [ 13 ]. In our community-dwelling population of older adults, we have previously shown that variants of the CYP19A1 gene, which codes for aromatase, the key enzyme in the conversion of androgen to estrogen, were susceptibility factors for LLD in women specifically [ 29 ]. We also just reported that variants of the CYP11B1 gene coding for 11-β hydroxylase, the next enzymatic step after CYP21A2 in steroidogenesis pathway, were susceptibility factors for LLD in women [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is relevant to mention that some single-nucleotide CYP19A1 polymorphisms increase the risk of late-life depression in women without a previous history of major depression, whereas other variants of the gene, associated with higher estradiol levels, decrease the risk of late-life depression in women with a history of major depression. 61 …”
Section: Physiological and Pathophysiological Function Of Brain Aromatasementioning
confidence: 99%